Management and Productivity: Foreign Conceptions and Verification Problem - E. L. Moreva (Управленческие науки)
The article contains the critical analysis of foreign methods of management research treated as a productivity factor and elaborated on the basis of surveys. The evaluation of such approaches is relevant for Russia because of its low economic productivity with the causes of management’s role keeping unclear. The article shows the first of such researches operated in some foreign countries and economic sectors seemed to prove the link between management and productivity while later applied to various countries and sectors they didn’t achieve the goal. The survey methods impeded the credible determination of the investigated link, its mechanism and terms of constitution. To cope these problems the complementation of such instrument with the others compensating its inability to identify the casualty of the links, the information distortion due to the peculiarities of the cognition processes reflected in the surveys and its limitations under multiplicity and variability of the management and productivity interaction in various national and sectoral contexts was required. These means were the tried and tested historical research methods as well as the new ones elaborated basis systemic approach for so called soft theories. Their application with the survey method would result in the constitution of the efficient instrument not only for the operative and reliable determination of the link between management and productivity of various sectors and countries but for the respective economic policy elaborated and realized on such a basis. To cope with these problems the complementation of such instrument with the others compensating its inability to identify the casualty of the links, the information distortion due to the peculiarities of the cognition processes reflected in the surveys and its limitations under multiplicity and variability of the management and productivity interaction in various national and spectral contexts was required. These means were the tried and tested historical research methods as well as the new ones elaborated basis systemic approach for so called soft theories. Their application with the survey method would result in the constitution of the efficient instrument not only for the operative and reliable determination of the link between management and productivity of various sectors and countries but for the respective economic policy elaborated and realized on such a basis.